Utilization Of Used Pet, Hdpe, And Pp Plastics As Raw Materials For 3d Printing Filaments: A Comparative Study Of Mechanical Properties And Storage Resistance At Room Temperature - Abinda, Azora Esya; Gantada, Muhammad Satya Putra (Green Publisher Indonesia, 2025)
This study investigates the feasibility of upcycling post-consumer polyethylene terephthalate (PET), high-density polyethylene (HDPE), and polypropylene (PP) wastes into 3D-printing filaments and comparatively evaluates their mechanical performance and storage durability at room temperature. Waste plastics were sorted, washed, dried, and extruded into 1.75 mm filaments under polymer-specific temperature profiles. Dimensional consistency was assessed through diameter measurements at multiple points, while tensile tests on filament specimens were conducted at 0, 30, 60, and 90 days of storage to determine ultimate tensile strength, elastic modulus, and elongation at break. The results show that all recycled filaments satisfy typical FDM dimensional tolerances, with rPET exhibiting the lowest coefficient of variation in diameter. At t = 0 days, rPET displays the highest tensile strength and modulus but the lowest ductility, rHDPE shows the highest ductility but lowest strength, and rPP presents intermediate behavior. During storage, all filaments undergo property degradation, yet with different rates: rPET retains ?90% of its initial strength and ?95% of its modulus after 90 days, whereas rHDPE and rPP experience larger reductions, particularly in ductility (to about 66–67% of their initial elongation at break). These findings demonstrate that common plastic wastes can be converted into technically viable FDM feedstock and reveal that rPET is the most robust option for applications requiring higher strength and longer shelf life, while rHDPE and rPP are better suited for flexible parts provided that storage conditions and inventory rotation are carefully controlled.